Pengaruh PSAK 108, Produk Unit Linked terhadap Asumsi Going Concern Perusahaan Asuransi Syariah di Indonesia - Nano Suyatna (ITB AAS INDONESIA Surakarta, 2021)
It is recommended that tomorrow's risk is anticipated in Islam, the applicant can use Sharia Life Insurance. The problem is the emergence of insurance companies that fail to pay, so that customer expectations are lost. This study aims to provide input in choosing the right insurance company and add insight for those interested in insurance. The research method used is descriptive quantitative research methods. The results showed that: a. the positive influence between the application of PSAK 108 and the survival of sharia insurance companies partially, b. the positive influence between unit-linked products and the viability of sharia insurance companies partially, c. the positive influence between the application of PSAK 108 and unit-linked products with the survival of the Islamic insurance company together. The viability of sharia insurance companies will survive, if the consistent implementation of article 108 and sharia unit-linked products that are safe from the influence of the JCI in investing, and use good governance. The fact is from the data that there are companies that have large liquid assets that still survive, but there are also insurance companies with low capital that remain strong (high risk high return) in maintaining the going concen assumption.